2002
DOI: 10.1038/sj.onc.1205113
|View full text |Cite
|
Sign up to set email alerts
|

Novel estrogen and tamoxifen induced genes identified by SAGE (Serial Analysis of Gene Expression)

Abstract: The breast cancer promoting e ects of estrogen and the chemopreventive e ects of tamoxifen are thought to be mediated by the estrogen receptor, a ligand-dependent transcription factor. Therefore, comprehensive analysis of gene expression pro®les following estrogen or tamoxifen treatment may help us better understand the role estrogen plays in tumorigenesis. We utilized SAGE (Serial Analysis of Gene Expression) technology to identify genes regulated by estrogen and tamoxifen in the ZR75-1 estrogen dependent bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 34 publications
2
84
0
Order By: Relevance
“…We therefore studied BT-474 cells in which PHD1 protein expression was relatively high under basal conditions (see Fig. 2B), and in which induction of PHD1 mRNA by estrogen stimulation had been reported (37). Following estrogen stimulation PHD1, but not PHD2 or PHD3, protein level was further induced ϳ2.5-fold (Fig.…”
Section: Phd Isoforms 1-3 Contribute To the Regulation Of Hif-1␣ Undementioning
confidence: 85%
See 1 more Smart Citation
“…We therefore studied BT-474 cells in which PHD1 protein expression was relatively high under basal conditions (see Fig. 2B), and in which induction of PHD1 mRNA by estrogen stimulation had been reported (37). Following estrogen stimulation PHD1, but not PHD2 or PHD3, protein level was further induced ϳ2.5-fold (Fig.…”
Section: Phd Isoforms 1-3 Contribute To the Regulation Of Hif-1␣ Undementioning
confidence: 85%
“…In particular relative PHD1 protein levels were substantially lower than predicted by relative PHD1 mRNA levels and were barely detectable in many cell lines. As other work had highlighted the expression of PHD1 mRNA in breast carcinoma BT-474 cells (37), and in the testis (29), we also examined BT-474 cells, and two other cell lines (833K and SuSa) of testicular origin (Fig. 2, B and C).…”
Section: Phd Isoforms Manifest Distinct Patterns Of Cellular Expression-mentioning
confidence: 99%
“…Determination of ER␣ target genes has recently been undertaken by using DNA microarrays, identifying hundreds of genes with altered expression upon E 2 treatment of human breast cancer cells (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, while providing information of the global action of E 2 in these cells, gene expression profiling can rarely discriminate between direct and indirect ER␣ targets.…”
mentioning
confidence: 99%
“…Interestingly, the EGL-9 domain that was reported to be the active domain in regulating HIF-1a is conserved in Falkor, which seems to be the mouse ortholog of human PHD1, suggesting that Falkor might have a similar role in mouse cells. In yet another study, PHD1, the human homolog of Falkor was cloned by SAGE as an estrogen-induced gene in a breast cancer cell line and was designated EIT-6 (Seth et al, 2002). In this study, EIT-6 was found to promote colony growth in a human breast cancer cell line.…”
Section: Discussionmentioning
confidence: 81%
“…During the course of this study, the human homologs of Falkor, SM-20, and a third family member were cloned by several groups, creating a conserved family of mouse and human proteins (Bruick and McKnight, 2001;Epstein et al, 2001;Seth et al, 2002;Taylor, 2001). …”
Section: Cloning Of Falkormentioning
confidence: 99%